Association of IL-1α (-889) and TNF-α (-309) Gene Polymorphisms with Chronic Periodontitis in Hilla City - Doaa H. Hassan (Journal of Global Pharma Technology, 2018)
Background: Periodontitis is a infectious disease leading to the destruction of periodontium including periodontal ligament and adjacent alveolar bone induced by periodontal pathogens biofilm. Materials and Methods: A total of 90 patients, 50 with chronic periodontitis (CP) and 40 normal subjects0referring to the clinic of collage of Dentistry, Babylon University, Hilla City, Iraq, were evaluated, TNF-α and IL-1α genotyping was performed by PCR)and analyzed by polyacrylamide gel. Results: polymorphism of  IL1α (-889) and TNFα(-308), The results showed that there was no (significant) allele frequency) difference between(patients and)control groups. Conclusion: The current study suggest that there is no association between IL1α (-889) and TNF-α 308 polymorphism and chronic periodontitis in this population.Keywords: Periodontitis, IL1α (-889), TNF-α 308, Genetic Polymorphism, PCR.